PENGARUH PENGUASAAN BAHASA INDONESIA TERHADAP PRESTASI AKADEMIK DALAM MATA KULIAH AKUNTANSI PADA MAHASISWA JURUSAN AKUNTANSI UNIVERSITAS NEGERI MEDAN - Brema Bastanta Perangin-angin; Cici Carnila Br Sitepu; Enita Catrine Br Sembiring; Goretti Lolina Pandiangan; Inda Helena Situmorang; Ayu Nadira Wulandari (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2025)
Indonesian language plays a crucial role in daily life and education, particularly at the higher education level. As the medium of instruction, proficiency in Indonesian significantly impacts students' academic achievement, including those in Accounting programs. This study aims to analyze the influence of Indonesian language proficiency on the understanding of course materials and the academic achievement of Accounting students at the State University of Medan. Employing a qualitative phenomenological approach, this research involved 36 student respondents currently taking Indonesian language courses. The findings indicate that strong Indonesian language skills are essential in helping students comprehend accounting concepts, read textbooks, and complete assignments and exams. The majority of respondents agreed that good Indonesian language skills support their academic success, especially in explaining exam answers and writing reports. Conversely, limited Indonesian language proficiency hinders students' ability to grasp complex accounting concepts. This study concludes that strong Indonesian language proficiency contributes significantly to improving students' academic achievement in accounting and provides recommendations for developing Indonesian language instruction that is more integrated with technical courses in the Accounting department.